Analisis Fisikokimia, Sensori, dan Mikrobiologi Produk Cookies Tepung Beras Cokelat Germinasi (TBCG) - Christina Mumpuni Erawati; Tjandra Pantjajani; Rahel Alfaniah (Jurnal Kesehatan Indonesia, 2025)
Some people experience health problems eating food products with wheat flour as the raw material. Brown rice sprouts or brown rice can be an alternative solution because it is easy to cook, has a softer texture, and a milder taste. This research is an experiment study of brown rice sprout cookies products whether they can replace cookies made from wheat flour. This study aims to evaluate the physicochemical, sensory, and microbiological characteristics of cookies made with germinated brown rice flour (GBRF) as a gluten-free alternative. The physicochemical tests included moisture content and water activity (Aw), physical tests included texture by texture analyzer and color by color reader, microbiological tests included Total Plate Count (TPC) and molds, also sensory evaluation to assess consumer acceptance. The results showed that cookies with 100% GBRF formulation had a moisture content of 3.70% and Aw of 0.42, meeting the SNI 2973:2018 standards. Microbiological tests showed that all samples were safe for consumption with TPC and mold values below the maximum SNI limits. Based on sensory evaluation which is included taste, color, teksture and aroma parameters, cookies with 100% GBRF were the most preferred by the panelists. In addition, the de garmo effectiveness index showed the best treatment,was cookies with formulation of 100% germinated brown rice flour (GBRF), indicating significant potential as a healthy and consumer-accepted gluten-free product.